Never the End: Narrating Future Ancestors in Cherie Dimaline’s The Marrow Thieves - Couch, Dylan (Cahier voor Literatuurwetenschap, 2024)
Drawing on Indigenous scholarship, this essay investigates two narrative implications of a spiraling sense of time in Cherie Dimaline’s The Marrow Thieves to explore how an Anishinaabe epistemology contends with past actions and events by placing characters in dialogue with ancestors. The Marrow Thieves presents a spiraling sense of time through the novel’s embedded oral tale, called Story, and dreams. The first argument I make in this essay is that the unique chronology posited by Story is such that it collapses concrete distinctions between the past and present, showing how ancestral experiences with settler colonialism inform characters’ present-day experiences. I then argue that spiraling narratives convey an intergenerational, collective voice that strengthens attachments to place and relationships with ancestors, community, and nonhumans. Spiraling time clarifies ways in which Indigenous characters respond to, and reflect on, the experiences of ancestors who endured previous apocalyptic events; it’s an intergenerational dialogue that supports a thriving Indigenous present and future.